Analysis of gender coloniality through Brazilian conceptual practices: Anna Bella Geiger’s Brasil Nativo/Brasil Alienígena (1977); and Rosana Paulino’s Amor pela Ciência (2016) - Cardoso, Renata Gomes; Oliveira, Deborah Moreira de (Revista do Colóquio, 2025)
This article explores Brazilian artistic works produced from the perspective of Latin American conceptualism, with an emphasis on women artists. In this context, we address works by Anna Bella Geiger and Rosana Paulino, seeking reflections that articulate subjective themes with structural issues, intertwining the political and social aspects of conceptual practices with identity intersections, concerning gender and race issues. We approach these articulations through the concepts of gender coloniality, as developed by the Argentinian sociologist Maria Lugones, enabling reflections on how this is reshaped in the poetics of the artists and in the political conditions of the social sphere. Thus, art is configured as a powerful device for investigating and denouncing the strategies of colonization for the subjugation and dehumanization of dissident cultures.